Reference point formation by market investors - Kliger, Doron; Kudryavtsev, Andrey (Journal of Banking & Finance, 2008)
The disposition effect [Shefrin, H., Statman M., 1985, The disposition to sell winners too early and ride losers too long. Journal of Finance, 40, 777–790], investors’ tendency to sell gaining assets and hold on to loosing assets, relies on the notion of a reference point distinguishing between losses and gains. While literature using aggregated market data documented the existence of such a reference point affecting investors’ decisions, it had not pinpointed it. The main goal of our work is to shed light on the mechanism of reference point formation. We hypothesize that salient events taking place during a stock’s holding period influence investors’ perceptions and make them update the stock’s reference point. Using analysts’ earnings forecasts, stock price data, and firms’ quarterly earnings announcements, we document that company-specific events indeed affect the reference points. We discover that the earnings announcements played a role in reference point formation when they were not anticipated, i.e., when (i) analysts’ earnings forecasts failed to provide accurate predictions; and (ii) the earnings announcements were followed by market price reactions. Moreover, the reference points were affected more profoundly for low market capitalization, high beta firms, pointing that the reference point updating process is more reactive to events when information flow is low and prices are sensitive to market fluctuations. Our results also corroborate the attention hypothesis, i.e., the observation that agents facing numerous alternatives may consider primarily those that have caught their attention.